Dynamic and balanced regulation of the thrABC operon gene for efficient synthesis of L-threonine - Hao, Ruxin; Wang, Sumeng; Jin, Xin; Yang, Xiaoya; Qi, Qingsheng; Liang, Quanfeng (Frontiers in Bioengineering and Biotechnology, 2023)
L-threonine is an essential amino acid used widely in food, cosmetics, animal feed and medicine. The thrABC operon plays an important role in regulating the biosynthesis of L-theronine. In this work, we systematically analyzed the effects of separating thrAB and thrC in different proportions on strain growth and L-threonine production in Escherichia coli firstly. The results showed that higher expression of thrC than thrAB enhanced cell growth and L-threonine production; however, L-threonine production decreased when the thrC proportion was too high. The highest L-threonine production was achieved when the expression intensity ratio of thrAB to thrC was 3:5. Secondly, a stationary phase promoter was also used to dynamically regulate the expression of engineered thrABC. This strategy improved cell growth and shortened the fermentation period from 36 h to 24 h. Finally, the acetate metabolic overflow was reduced by deleting the ptsG gene, leading to a further increase in L-threonine production. With these efforts, the final strain P2.1-2901ΔptsG reached 40.06 g/L at 60 h fermentation, which was 96.85% higher than the initial control strain TH and the highest reported titer in shake flasks. The maximum L-threonine yield and productivity was obtained in reported fed-batch fermentation, and L-threonine production is close to the highest titer (127.30 g/L). In this work, the expression ratio of genes in the thrABC operon in E. coli was studied systematically, which provided a new approach to improve L-threonine production and its downstream products.